Qual a relação entre salário dos docentes e os resultados da educação básica? - Moreira, Gustavo Pinheiro (2018)
The search for better educational outcomes in Brazil has been reflected in increasing investments in the area in the last two decades, in this context, the dimension of investment in education gains centrality in academic debates. In view of the representativeness of salaries in total expenditure, the discussion about the relationship between salaries and the quality of the education provided becomes urgent. Thus, the present work sought to establish a relationship between the remuneration of municipal teachers and educational indicators of flow and academic performance through regression analysis and quantile regression. The results point to a non-linear relationship between these two variables. On the one hand, the fulfillment of the National Magistries Floor has positive effects on school performance and flow, but on the other hand, there is a negative correlation between the wage value and these indicators. It follows from this that a level is likely to exist, from which the rise in wages tends to lose relevance.